You should use first linearity of integral such that:

` int (3x)/(x^2+2)dx + int 1/(x^2+2)dx`

You need to use substitution to solve the integral `int (3x)/(x^2+2)dx ` such that:

`x^2 + 2 = t => 2xdx = dt => xdx = (dt)/2`

`int (3x)/(x^2+2)dx = 3 int (dt)/2/t `

`3 int (dt)/2/t = (3/2) int (dt)/t => (3/2) int (dt)/t = (3/2)ln|t| + c`

Substituting back `x^2 + 2` for `t` yields:

`int (3x)/(x^2+2)dx = (3/2)ln(x^2 + 2) + c`

`int (3x+1)dx/(2+x^2) = (3/2)ln(x^2 + 2) + int 1/(x^2+2)dx`

You need to use the following formula to solve `int 1/(x^2+2)dx` such that:

`int 1/(x^2+a^2)dx = (1/a)tan^(-1)(x/a) + c`

Reasoning by analogy yields:

`int 1/(x^2+2)dx = (1/sqrt2)tan^(-1)(x/sqrt2) + c`

`int (3x+1)dx/(2+x^2) = (3/2)ln(x^2 + 2) +(1/sqrt2)tan^(-1)(x/sqrt2) + c `

**Hence, evaluating the given integral yields `int (3x+1)dx/(2+x^2) =
(3/2)ln(x^2 + 2) + (1/sqrt2)tan^(-1)(x/sqrt2) + c.`**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.